Molecular cloning and expression of EgTCTP, encoding a calcium binding protein, enhances the growth of callus in oil palm (Elaeis guineensis, Jacq) - Alisa Nakkaew; Wilaiwan Chotigeat; Amornrat Phongdara (Songklanakarin Journal of Science and Technology (SJST), 2010)
The translationally controlled tumor protein (TCTP) has now been identified in evolutionarily diverse organisms and isthought to play an important role in cell growth and cell division. We have identified an EgTCTP gene from Elaeis guineensisJacq. It is a putative protein of 168 amino acids with a calculated molecular mass of 19.2 kDa. EgTCTP has a high homology(84% - 91% identity) at the amino acid level to other plant TCTPs from Hevea brasiliensis, Arachis hypogaea and Glycinemax. The recombinant EgTCTP protein is a calcium binding protein. Transgenic embryonic calli overexpressing EgTCTP havea faster growth rate than non-transformed and empty vector transformed calli. The results show that the enhancement ofEgTCTP gene expression in oil palm embryogenic calli may result in faster multiplication of the embryogenic calli. EgTCTPacts as another Ca2+-modulated protein that is involved in the cell cycle progression.